Antibiotic Discovery from the Abyss - Stennett, Henry (Cranfield University, 2020)
It is essential that we discover and develop new antibiotics to overcome the problems associated with antibiotic resistance and find treatments for bacteria that don’t respond well to currently available treatment options. Recent years have seen revived interest in culture-dependent methods for discovery - screening rare bacteria from unexplored environments for their ability to inhibit the growth of pathogens. The deep sea is vast, rich in biodiversity, and one of the few ‘pristine’ environments on the planet. The extremophilic bacteria from this niche are likely metabolic innovators that evolved differently to terrestrial species, making them attractive sources of novel natural products.Our aims include (i) characterising the microbiome of deep-sea sponges, which have never been investigated before; (ii) culturing deep-sea bacteria and screening them for antibiotic production; (iii) genome sequencing and mining of producers to delineate the biosynthesis of novel antibiotics. This interdisciplinary project involves microbiology, bioinformatics, and analytical chemistry techniques.A recent screen of bacteria isolated from deep sea sponges found six strains that produce antibiotics under specific culture conditions. The genomes of these bacteria have been sequenced with Illumina and Nanopore technologies, and several active molecules have been purified. Our hit rate (8/487, or 1.6%) is higher than estimated for other environments, indicating that deep-sea sponges are a powerful source of biodiversity. Future work will involve linking natural products to biosynthetic gene clusters and transferring these clusters to heterologous hosts for larger scale production of antibiotics for method-of-action and efficacy studies.
Keywords: 'Antibiotics'; 'Drug'; 'Discovery'; 'DSDS19'; 'DSDS19 Poster'; 'Microbiology'; 'Bioinformatics'; 'Analytical Chemistry not elsewhere classified'